The Unresolved Legality of Online Gambling in Singapore - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2011)
This article addresses what appears to be a hitherto (legislatively and judicially) unresolved issue in a country where gambling is an established sub-culture – the legality of online gambling. The existing legislation does not provide direct answers, and as a result, the courts have not been given the opportunity to answer the question directly either. The police have previously made a few statements to the press and the media, but what should we make of them? While placing bets with unauthorised bookies (including those who operate their own website or use others’ websites) is clearly outlawed, leaving the offender with no excuse if caught, the situation surrounding personal online gambling is much more ambiguous – and this is not just due to unclear legislation. The statistics on Singaporeans who gamble online may not be forthcoming, but it is a sure bet that there is a substantial – and growing – number. Is there really any good reason not to make the law clearer? This article not only considers the legal position, but prefaces that with a discussion of the various factors that lend online gambling a sense of allure and ostensible legitimacy.